2011
DOI: 10.1088/2041-8205/731/1/l14
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Neutral Hydrogen on Cosmic-Ray Precursors in Supernova Remnant Shock Waves

Abstract: Many fast supernova remnant shocks show spectra dominated by Balmer lines. The Hα profiles have a narrow component explained by direct excitations and a thermally Doppler broadened component due to atoms that undergo charge exchange in the post-shock region. However, the standard model does not take into account the cosmic-ray shock precursor, which compresses and accelerates plasma ahead of the shock. In strong precursors with sufficiently high densities, the processes of charge exchange, excitation and ioniz… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 49 publications
(78 reference statements)
2
31
0
Order By: Relevance
“…A first effort to include neutrals in the shock acceleration theory was made by Wagner et al (2009) using a two-fluid model to treat ions and CRs, but neglecting the dynamical role of neutrals. A different model was A&A 562, A141 (2014) proposed by Raymond et al (2011): here momentum and energy transfer between ions and neutrals are included, but both the CR spectrum and the profile of the CR-precursor were assumed a priori rather than calculated selfconsistently. Blasi et al (2012) proposed a semianalytical kinetic calculation that returns the distribution function of neutral hydrogen atoms in the absence of accelerated particles and all thermodynamical properties of the ion plasma.…”
Section: Introductionmentioning
confidence: 99%
“…A first effort to include neutrals in the shock acceleration theory was made by Wagner et al (2009) using a two-fluid model to treat ions and CRs, but neglecting the dynamical role of neutrals. A different model was A&A 562, A141 (2014) proposed by Raymond et al (2011): here momentum and energy transfer between ions and neutrals are included, but both the CR spectrum and the profile of the CR-precursor were assumed a priori rather than calculated selfconsistently. Blasi et al (2012) proposed a semianalytical kinetic calculation that returns the distribution function of neutral hydrogen atoms in the absence of accelerated particles and all thermodynamical properties of the ion plasma.…”
Section: Introductionmentioning
confidence: 99%
“…The first attempt to model this scenario was done by [12] using a two-fluid approach to treat ions and CRs but neglecting the dynamical role of neutrals. A different model was proposed by [13] where momentum and energy transfer between ions and neutrals is included, but the profile of the CRprecursor is assumed a-priori . Both works concluded that the observed width of 30-50 km s −1 can be explained using a low CR acceleration efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The sensitivity of the broad-to-narrow ratio to preshock neutral fraction and cosmic ray acceleration efficiency is yet to be studied theoretically in full detail. The Balmer models show that a moderate efficiency of cosmic ray acceleration, CR ∼0.2, is necessary for widening the narrow component line profile and collisionally exciting Hα in the cosmic ray precursor (Vink et al 2010;Raymond et al 2011). The broad component width and broad-to-narrow flux ratio, formerly a diagnostic of shock speed, neutral fraction and electron-ion equilibration, have now been shown to depend on CR as well.…”
Section: Discussionmentioning
confidence: 99%